(untitled) (GEOgraphia, 2010)
A partir do entendimento da categoría de utopía num viés territorial, o artigo aborda o debate sobre a relação entre utopia e territorio na contemporaneidade e como se vislumbram algumas das perspectivas que tentaram resolvê-lo. Abstract From the understanding of the category of utopia in a territorial sense, this article focus the debate on the relation between utopia and territory and how to understand some of the different approaches trying to resolve them.